Transformation of tetracycline antibiotics with goethite: Mechanism, kinetic modeling and toxicity evaluation. (1st July 2021) - Li, Jingchen; Zhao, Lin; Zhang, Ruochun; Teng, H. Henry; Padhye, Lokesh P.; Sun, Peizhe
Highlights: Goethite can transform tetracyclines under various environmental conditions. Two different hydroxyl groups on goethite were reactive sites for TTC degradation. N, N-dedimethylation was the major transformation pathway for TTC. Antimicrobial properties of TTC were eliminated after transformation by goethite. Dealkylation by goethite are expected for other drugs possess alkylamino group. Abstract: Tetracycline antibiotics (TCs) are a group of the top selling and widely used antibiotics that have been frequently detected in various environments. The interaction between TCs and goethite (α-FeOOH), one of the most common crystalline oxide minerals in aqueous environment and soil, is unclear. Apart from adsorption, this study firstly demonstrated that transformation of tetracycline (TTC) occurred in the presence of goethite. The transformation kinetics and mechanism of TTC with goethite were investigated to gain a better understanding of the fate of TCs in the natural environment. The results showed that the transformation of TCs by goethite explicitly exhibited two-stage kinetics, wherein an initial period of fast transformation was followed by a continuous slow transformation. Hydroxyl groups on goethite were identified as major reactive sites, among which singly coordinated hydroxyls (FeOH) were more reactive than doubly coordinated hydroxyls (Fe2 OH) towards the transformation of TTC. On the basis of transformation rates, speciation of TTC and functional groups on goethite surface, a kinetic model was established successfully describing the transformation of TTC by goethite under conditions of varying reactant concentration and pH. The transformation of TTC by goethite mainly resulted in a N, N-dedimethylation product that did not show antimicrobial properties towards Escherichia coli . This study indicates that Fe(III)-(hydro)oxides in soils and sediments may play an important role in the natural attenuation of tetracycline antibiotics and their bioactivity. Graphical abstract: Image, graphical abstract